Aktivitas Ekonomi Masyarakat Miskin di Desa Tamaila Utara Kecamatan Tolangohula Kabupaten Gorontalo - Zenab S. Tadu; Roy Hasiru; Agil Bahsoan (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This studyaims to examine the economic activities of low-income communities and identify factors that influence these activities in Tamaila Utara Village,Tolangohula Sub-district,Gorontalo Regency. The study employed a qualitative method using a systematic approach. Data collection techniques included observation, interview, and source triangulation.Data analysis involved data reduction followed by drawing conclusions. The findings indicate that most low-income residents in Tamaila Utara rely on agriculture, particularly corn farming, as their primary livelihood. Farming activities are supported by family members due to limited financial capacity to hire labor, and the tools used are still very simple or traditional. For crop distribution,the community depends on local traders who offer prices significantly lower than market rates, due to limited transportation access to larger markets. In terms of consumption,residents can only meet their basic needs, with low nutritional intake due to minimal income. Other challenges to improving the local economy include water scarcity during the dry season, low educational attainment among farmers,lack of government-provided training, and unpredictable weather and environmental conditions. Therefore,government support is urgently needed,such as irrigation development, agricultural training, and the provision of modern tools or technology to enhance community welfare in the future.